2015
DOI: 10.13168/agg.2015.0037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study on Bearing Capacity of Conical Shell Foundations Composed of Reactive Powder Concrete

Abstract: Many forms of shells are available for use as foundations. Then frustum of a cone in the upright position can serve as footing for columns or raft for structure such as chimneys. Reactive Powder Concrete (RPC) is an ultra-high strength, low porosity material with high cement and silica fume contents and steel fibers. The present study aims at studying the RPC as a material used to construct RPC shell foundations. A complete load-frame assembly was designed and fabricated for experimental work. Experimental tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Also, the reduction of bearing capacity has been observed due to the increase in the burial depth of geotextile layers. Furthermore, the investigations indicated that the failure wedge of shell foundations in reinforced backfill conditions is formed deeper than that of conventional flat ones [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the reduction of bearing capacity has been observed due to the increase in the burial depth of geotextile layers. Furthermore, the investigations indicated that the failure wedge of shell foundations in reinforced backfill conditions is formed deeper than that of conventional flat ones [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of China's infrastructure, more and more transmission lines are being built in mountainous and high mountain areas, where the tower foundation plays an important role in the construction of transmission lines due to limited construction space and large-scale construction equipment, such as the anchor foundation [1], conical shell foundations [2]. The digging hold foundations are quite popular for special geological conditions and harsh construction environments due to their high bearing capacity and easy construction, which has been widely applied in mountainous and high mountain areas.…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has primarily focused on treating recycled concrete and examining its properties, there is a lack of studies on the performance of structural members made from recycled concrete (RAC), such as beams, columns, joints, and frames. [5][6][7] 2. Literature…”
Section: Introductionmentioning
confidence: 99%